Cochrane Database of Systematic Reviews 2006
DOI: 10.1002/14651858.cd005627
|View full text |Cite
|
Sign up to set email alerts
|

Diet or exercise, or both, for weight reduction in women after childbirth

Abstract: Background Weight retention after pregnancy may contribute to obesity. It is known that diet and exercise are recommended components of any weight loss programme in the general population. However, strategies to achieve healthy body weight among postpartum women have not been adequately evaluated. Objectives The objectives of this review were to evaluate the effect of diet, exercise or both for weight reduction in women after childbirth, and to assess the impact of these interventions on maternal body composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 27 publications
3
40
0
2
Order By: Relevance
“…Preliminary findings of a recently published Cochrane review (16) extracted from six studies showed that among women recruited in the postpartum period (up to 12 months postpartum) a prescribed diet combined with structured exercise, or diet alone, compared with usual care, seemed to enhance weight loss (16) . However, this Cochrane review focused on the effect of a change in diet or exercise on change in weight without examining the factors that lead to behaviour change.…”
Section: Physical Activity Healthy Eating Weight Change Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Preliminary findings of a recently published Cochrane review (16) extracted from six studies showed that among women recruited in the postpartum period (up to 12 months postpartum) a prescribed diet combined with structured exercise, or diet alone, compared with usual care, seemed to enhance weight loss (16) . However, this Cochrane review focused on the effect of a change in diet or exercise on change in weight without examining the factors that lead to behaviour change.…”
Section: Physical Activity Healthy Eating Weight Change Interventionsmentioning
confidence: 99%
“…The main reasons for exclusion were lack of a control group; a different outcome measurement than physical activity or nutritional behaviour; or because mothers of children above 5 years of age were included in the study. Moreover, four review articles were found, all describing studies which mainly investigated the relationship between weight-related behaviours and weight only using prescribed diet or exercise with no attention for lifestyle change (16,(20)(21)(22) . Equally, two intervention studies were excluded for this reason.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protective factors are less well studied, but include modifiable behavioural strategies such as healthy diet and physical activity (12)(13)(14)(15) and mode of infant feeding.…”
mentioning
confidence: 99%
“…Evidence on postnatal interventions is developing, with systematic reviews reporting that interventions which combined diet and physical activity components were more likely to be successful (van der Pligt et al, 2013, Amorim et al, 2007. Vincze et al (2017) explored motivators for healthy eating and physical activity among women in Australia who had given birth in the previous five years.…”
Section: How Do Included Papers Contribute To the Evidence?mentioning
confidence: 99%